Molecular characterization of trypanosomes commonly found in cattle, wild animals and tsetse flies in Kwazulu-Natal, South Africa, 2005-2007 - Majiwa, P.A.O. (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2008.